Sir Cumference and the Isle of Immeter : A Math Adventure - Cindy Neuschwander (Watertown, United States Charlesbridge Publishing,U.S., 2006)
When young Per visits her uncle Sir Cumference and his family, she learns how to play the game, "Inners and Edges." After she finds a clue linking the game to the mysterious castle on the island of Immeter, she must figure out how to find the perimeter and area of a circle to unlock the island's secret. Math skills taught include finding the area and perimeter of a rectangle and a circle. Introduces an underlying concept of calculus -- using straight lines to measure curves.